Aquisição de apontações pronominais pessoais em língua brasileira de sinais (LIBRAS) - Grutzmacher, Marcos (2019)
Pointings are very productive elements in Libras. They may indicate locations, in addition to referents present or absent in speech, linguistically equivalent to personal pronouns, among other functions (CORMIER; SCHEMBRI; WOLL, 2013). They can also be found in other sign languages such as ASL and the Greek Sign Language. So since these language forms are also found in Libras, what would be their acquisition path? Would there be differences between your acquisition in Libras and other languages (oral and gestural)? Our research is based on the innate assumptions defended by Chomsky's Generative Theory (1994 [1987]) and aims to describe the acquisition of pronominal pointing in Libras through a case study of a deaf child born to parents. This deaf people were acquiring Libras as their first language. Our specific objectives were: perform a survey of the pointing made; select the productions of pointing related to verbs, checking the path of acquisition of these pointing; analyze in which syntactic position, whether subject or object, the pronominal pointing appear; classify the stage of acquisition of the pointing. Our corpus consisted of video recordings of the spontaneous production of a deaf child, ranging from 1:07 to 3:03 years of age. We looked at five videos of about 30 to 40 minutes each. Our findings showed that the deaf child acquiring Libras went through the same stages of pronoun acquisition as children in other oral languages, as well as the same stages of acquisition of pronominal notations in other sign languages.